Pengaruh Keputusan Investasi Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada PT Mitra Adiperkasa TBK Periode 2013-2024 - Dijan Mardiati (Journal of Innovative and Creativity, 2025)
This quantitative research, utilizing panel data regression, examines the impact of Investment Decisions (measured by TAG) and Dividend Policy (measured by DPR) on Firm Value (measured by PBV) at PT Mitra Adiperkasa Tbk from 2013–2024. The analysis reveals that partially, Dividend Policy (DPR) positively and significantly affects Firm Value, aligning with the Signaling Theory, whereas Investment Decisions (TAG) show no significant effect. Nevertheless, both variables collectively demonstrate a significant simultaneous influence on Firm Value. The key implication for MAPI management is the necessity to prioritize stability and transparency in dividend policy as a fundamental strategy to maintain investor confidence and drive an increase in firm value.